A Survey on the Impact of COVID-19 on Lacrimal Surgery: The Asia-Pacific Perspective - Nair AG (Dove Medical Press, 2020)
Akshay Gopinathan Nair,1,2 Natasha Narayanan,3 Mohammad Javed Ali4 1Ophthalmic Plastic Surgery and Ocular Oncology Services, Aditya Jyot Eye Hospital, Mumbai 400 031, India; 2Advanced Eye Hospital & Institute, Navi Mumbai 400 705, India; 3Temple University, Philadelphia, PA 19122, USA; 4Govindram Seksaria Institute of Dacryology, L.V. Prasad Eye Institute, Hyderabad, Telangana 600 034, IndiaCorrespondence: Akshay Gopinathan NairOphthalmic Plastic Surgery and Ocular Oncology Services, Aditya Jyot Eye Hospital, 153 Major Parmeswaran Road, Wadala, Mumbai 400 053, IndiaTel +91-22-2417 7600Email akshaygn@gmail.comAim: To assess the impact of the COVID-19 pandemic-related lockdown on lacrimal surgery among oculoplastic surgeons in the Asia-Pacific region.Methods: An institutional board review approved anonymous electronic survey was sent out via email to oculoplastic surgeons across the Asia-Pacific region. All responses were tabulated and analysed.Results: A total of 259 valid responses were received. Nearly 87% of the surgeons agreed that lacrimal procedures were associated with a high risk of COVID-19 transmission. In all, at the time of taking the survey, 151/259 (58.3%) of the surgeons were not performing any lacrimal surgeries in view of the COVID-19 pandemic and 71/259 (27.4%) of the respondents were only performing emergency lacrimal surgeries. External dacryocystorhinostomy was the most commonly performed lacrimal procedure across the region and lacrimal procedures contributed to at least 25% of the income for nearly a third of the respondents. Majority of the respondents were female (52.9%), but a significantly higher proportion of male oculoplastic surgeons were still performing lacrimal surgeries during the lockdown. Over 75% of respondents indicated that resuming lacrimal procedures is important to their practice.Conclusion: The survey showed that there was a general agreement among the surveyed oculoplastic surgeons in the Asia-Pacific region that lacrimal procedures were associated with a high risk of COVID-19 transmission and over 85% of them of had either stopped performing elective lacrimal surgeries altogether or were providing only emergent care. It is likely that not performing elective lacrimal procedures, COVID-19 has financially impacted a high percentage of the surveyed oculoplastic surgeons.Keywords: dacryocystorhinostomy, dacryology, coronavirus, epiphora, economic impact